Primary Adrenocortical Insufficiency Case Series in the Neonatal Period: Genetic Etiologies Are More Common Than Expected - Jinzhi Gao; Ling Chen (Frontiers Media S.A., 2020)
Primary adrenocortical insufficiency (PAI) is an important cause of morbidity in neonates. The most common cause of PAI in neonates is congenital adrenal hyperplasia (CAH) due to 21-hydroxylase deficiency (21-OHD). Other rarer monogenic cases, for example, adrenal hypoplasia congenita (AHC) or familial glucocorticoid deficiency, also simulate clinical manifestation of 21-OHD, leading to misdiagnosis. The therapies and prognosis of these monogenic cases of PAI are entirely different. This study aimed to compare the differences of clinical data and identify genetic etiologies of PAI cases in the neonatal period. All 7 neonates initially presented with hyperpigmentation, hyponatremia, hyperkalemia, and high serum adrenocorticotropic hormone levels. Only CAH patients showed hyperandrogenism and remarkably elevated serum 17-hydroxyprogesterone levels. All the pathogenic mutations found in CYP21A2 were well known, except c.1069C>T (exon 8). The male patient with AHC had a novel hemizygous deletion of exon 2 in DAX1. The other one with familial glucocorticoid deficiency type 1 had two novel heterozygous mutations in the gene coding melanocortin 2 receptor, c.701C>T (exon 2) and c.119delT (exon 2). Glucocorticoid and/or mineralocorticoid replacement therapy depends on the cause of PAI. Genetic testing can be performed as a alternative diagnostic approach to provide information about therapy, prognosis, and genetic counseling.